Detection of zoonotic pathogens in animals performed at the University Hospital Institute Méditerranée Infection (Marseille – France) - Bernard Davoust (One Health, 2021)
At the University Hospital Institute Méditerranée Infection (IHU, Marseille, France), for almost thirty years, veterinarians have been carrying out epidemiological investigations, together with doctors, on animals living near human cases of zoonoses, on the one hand, and on the other hand, transverse and longitudinal epidemiological surveillance studies on animals which are reservoirs, vectors or sentinels of potentially zoonotic infections,. This article presents the methods adopted and the results obtained from these studies. They have been the subject of 76 peer-reviewed publications relating to wild animals (37 publications) and/or domestic animals (48 publications). These studies were often carried out in the field with veterinarians from the French army's health service (39 publications). They were at the origin of the detection of some thirty zoonotic pathogens in the laboratories of the IHU (64 publications) and/or other French laboratories (18 publications). Our approach is an original embodiment of the “One Health” concept.